Lipid-based carriers for controlled delivery of nitric oxide - Elnaggar, Mahmoud A.; Subbiah, Ramesh; Han, Dong Keun; Joung, Yoon Ki (Ashley Publications Ltd., 2017)
Introduction: Nitric oxide (NO) is crucial for body homeostasis at moderate levels, but cytotoxic at high levels, thus making it a potential candidate for anticancer therapies and antibacterial surface coatings. To date, NO use has been limited due to its very short half-life. Many strategies have been utilized in an attempt to control the half-life of NO, including (but not limited to) lipid-based carriers, due to their biocompatibility and versatility. Areas covered: In this review, we discuss the latest studies that aimed to control the release of NO via a variety of lipid-based delivery carriers, such as liposomes (echogenic and normal) and microbubbles. In addition, we discuss the different types of NO donors used to control and target the release of NO. Expert opinion: Achieving a NO releasing lipid-based systems to mimic the natural release rate of NO remains a challenging task. Many promising strategies are still to be tackled, such as NO release supported lipid bilayers using GPx mimicking catalysts instead of vesicles, or the use of lipophillic NO donors such as nitrooleate instead of the conventional hydrophilic NO donors. These new strategies may present us with better alternatives to the previously published systems.